Niẓām al-Qur’ān and the Unveiling of Qur’anic Maqāṣid: An Epistemological Study of Structural Tafsīr in Farrin and Chishti - Miatul Qudsia; Jauhara Albar Rouhullah (Basmala: Journal of Qur’an and Hadith, 2025)
This article examines the relationship between the niẓām al-Qurʾān approach and the elucidation of the maqāṣid al-Qurʾān through an epistemological analysis of two contemporary structural tafsīr works: Structure and Qur’anic Interpretation by Raymond Farrin and Macro Structure of the Soorahs of the Holy Qur’an by Khaleel Ur Rahman Chishti. The study is predicated on the premise that structural analyses of the Qur’an serve not only to demonstrate textual coherence but also possess hermeneutic potential for uncovering the internal purposes of individual sūrahs. Employing a qualitative methodology grounded in literature review and epistemological scrutiny of tafsīr, this article investigates the sources of knowledge, methodological approaches, epistemological orientations, and interpretive validity of the two scholars. The findings indicate that Farrin advances a textual-structural epistemology that effectively maps the internal coherence and symmetry of the sūrahs, albeit yielding maqāṣid that are primarily descriptive in nature. Conversely, Chishti offers a normative-teleological epistemology explicitly oriented toward the maqṣad aʿẓam (the supreme purpose) of the sūrahs, although his structural framework is less formally theorized. This article contends that synthesizing Farrin’s structural rigor with Chishti’s normative orientation facilitates the development of a more comprehensive niẓām al-Qurʾān–based tafsīr capable of elucidating the maqāṣid al-Qurʾān. These findings contribute to advancing methodological dialogue between structural Qur’anic studies and maqāṣid discourse within contemporary Qur’anic scholarship. [Artikel ini mengkaji hubungan antara pendekatan niẓām al-Qur’ān dan penjelasan maqāṣid al-Qur’ān melalui analisis epistemologis terhadap dua karya tafsir struktural kontemporer: Structure and Qur’anic Interpretation oleh Raymond Farrin dan Macro Structure of the Soorahs of the Holy Qur’an oleh Khaleel Ur Rahman Chishti. Studi ini didasarkan pada premis bahwa analisis struktural terhadap Al-Qur’an tidak hanya berfungsi untuk menunjukkan koherensi tekstual tetapi juga memiliki potensi hermeneutik dalam mengungkap tujuan internal dari surah-surah individual. Dengan menggunakan metodologi kualitatif yang berlandaskan tinjauan pustaka dan pemeriksaan epistemologis terhadap tafsir, artikel ini menyelidiki sumber pengetahuan, pendekatan metodologis, orientasi epistemologis, dan validitas interpretatif dari kedua cendekiawan tersebut. Temuan menunjukkan bahwa Farrin mengembangkan epistemologi tekstual-struktural yang secara efektif memetakan koherensi internal dan simetri surah-surah, meskipun menghasilkan maqāṣid yang terutama bersifat deskriptif. Sebaliknya, Chishti menawarkan epistemologi normatif-teleologis yang secara eksplisit berorientasi pada maqṣad a‘ẓam (tujuan tertinggi) surah-surah, meskipun kerangka strukturalnya kurang secara formal diterapkan dalam teori. Artikel ini berpendapat bahwa mensintesis ketelitian struktural Farrin dengan orientasi normatif Chishti memfasilitasi pengembangan tafsir berbasis niẓām al-Qur’ān yang lebih komprehensif dan mampu mengungkap maqāṣid al-Qur’ān. Temuan ini berkontribusi dalam memajukan dialog metodologis antara studi struktural Al-Qur’an dan diskursus tentang maqāṣid dalam kajian Al-Qur’an kontemporer.]